Transitioning from National Examinations to Computer-Based National Assessments: Teachers'-Students' Perceptions and the Impact on Islamic Education - Noptario; M Hulkin; bin Nordin, Ts. Saiful Nazri (HEUTAGOGIA: Journal of Islamic Education, 2023)
This study delves into the shift from the traditional National Examination (NE) to the computer-Based National Assessment (CBNA) in Indonesia, focusing on the intricate implications for Islamic education. This study aims to explore the perceptions of teachers and students regarding the elimination of NE and the implementation of ANBK as a national standard. The research method used was qualitative, with interviews with principals, teachers, and students as the primary informants. While recognizing the benefits, the study highlights significant challenges, particularly alignment with Islamic values, infrastructure limitations, and concerns in remote regions. The findings, drawn from the experience of Madrasah Ibtidaiyah Ogan Ilir, serve as a microcosm of broader challenges, offering valuable insights for policymakers, educators, and stakeholders. The implications are extensive and multifaceted and require a balanced approach that preserves the unique identity of Islamic education. The study acknowledges limitations, including potential bias in participant sampling and regional focus, and recommends further research to provide a more comprehensive view. Collaboration and dialogue are vital for a successful transition that aligns with Islamic education's traditions and principles.